WHAT DRIVES DRINKING WATER AND SANITATION CHOICES AMONG AGRICULTURAL HOUSEHOLDS? CASE STUDY FROM NIGERIA - Aminu, Raheem O.; Oyawole, Funminiyi P.; Ibrahim, Shakirat B.; Arowolo, Aisha O. (FUDMA JOURNAL OF SCIENCES, 2025)
Access to clean drinking water and sanitation are fundamental human rights globally. This study aimed to determine the socio-demographic and location factors influencing the agricultural households’ choices of drinking water sources (DWS) and sanitation facilities in Nigeria. Data was obtained from the fourth wave of the Nigerian Living Standard Measurement Study, Integrated Survey on Agriculture (LSMS-ISA), and analysed using descriptive statistics and a multinomial logistic model. Total number of rooms in a dwelling, proximity to water sources, electricity access, household education levels, household size, gender of the household head, age of the household head, marital status, residential location, wealth index, and regional variations are among the significant factors influencing access to drinking water sources and sanitation facilities. Rural households and those in the country’s North-Central region are more exposed to open defecation than their counterparts in other locations. Based on the findings, we recommend that the stakeholders intensify efforts to provide access to electricity, introduce pro-poor policies and programmes, bridge the locational disparity, and introduce deliberate policy interventions, as these can improve access to drinking water and sanitation in Nigeria.